AIRBORNE MARITIME SURVEILLANCE IN THE NORTH ATLANTIC norwegian and allied patrols, 1945 to... the present-day. - BIRKELAND, JOHN O. (Cass series. Naval policy and history, 2025)
This book offers a comprehensive examination of historical Norwegian and allied airborne maritime surveillance operations in the North Atlantic, after World War II until the present.Russia's resurgent naval and submarine activity in the High North needs to be closely observed. Norway, together with her closest allies, have monitored such activity in the High North since the end of World War II. One of the key instruments in that effort has been Maritime Patrol Aircraft (MPA), with their Anti-Submarine Warfare (ASW) capabilities. However, after the Cold War, in many nations an atrophy took place within the MPA communities of knowledge, resources, and experience with airborne ASW. This occurred just as the concept of intelligence, surveillance and reconnaissance (ISR) came to play an increasingly important role in modern warfare, but without sufficient attention being paid to the specific challenges of maritime airborne surveillance and reconnaissance. This book addresses that gap and examines the entwined evolution of airborne maritime surveillance by MPA and ASW in the High North, both during and after the Cold War, with the main focus being on Norway. The discussion identifies the fundamental 'building blocks' of these historical surveillance operations through a portrayal of the development of airborne surveillance and reconnaissance operations. These building blocks are then applied to make recommendations for the future for maritime surveillance in the High North.This book will be of much interest to students of naval history, strategic studies, intelligence studies, Nordic studies and International Relations.